Differences in occupational stress by smoking intensity and gender in cross-sectional study of 59 355 Japanese employees using the Brief Job Stress Questionnaire (BJSQ): the Niigata Wellness Study - Kazuya Fujihara; Masaru Kitazawa; Satoru Kodama; Kiminori Kato; Hirohito Sone; Shigemi Tashiro; Minoru Tashiro; Kazuhiro Matsuda; Masato Otsuka; Koji Sato (BMJ Open, 2022)
Objectives It has been hypothesised that smoking intensity may be related to occupational stress. This study aimed to investigate whether stress, including problems with superiors or co-workers, is a driver of smoking.Design Cross-sectional study.Setting and participants 59 355 employees (34 865 men and 24 490 women) across multiple occupations who completed a self-reported questionnaire-based occupational stress survey between April 2016 and March 2017 in Niigata Prefecture.Main outcome measures Stress scores for the Brief Job Stress Questionnaire subscales summed up after assigning high points for high stress and converted to Z-scores based on the mean of all participants. Heavy smokers (HS) smoked ≥15 cigarettes/day and light smokers (LS) smoked <15 cigarettes/day and were compared with non-smokers (NS) by gender.Results The main subscale items that were significantly associated with smoking status in both genders included ‘physical burden’, ‘irritation’ and ‘physical symptoms’. In the analysis that included smoking intensity, the stress score for ‘co-workers’ support’ was significantly lower for LS men than NS men (NS 0.091±0.98, LS −0.027±1.00, HS 0.033±0.99), and was significantly higher for HS women than NS women (NS −0.091±1.00, LS −0.080±1.05, HS 0.079±1.03). However, the stress score for ‘co-workers’ support’ was low among LS women aged ≤39 years in the manufacturing industry.Conclusions It was speculated that LS men and some LS women gained ‘co-workers’ support’ using smoking as a communication tool while reducing the degree of smoking. The existence of such ‘social smokers’ suggested that to promote smoking cessation, measures are essential to improve the communication between workers in addition to implementing smoking restrictions in the workplace.